2014
DOI: 10.4103/0973-1075.125548
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of opioid drugs in Thai government hospitals: Thailand national survey 2012

Abstract: Context:Palliative care in Thailand was not well developed in the past. Previous studies showed that the actual prescription of opioids was underutilized in palliative care by physicians compared with the estimated opioid need of patients. However, there were no studies regarding the regulation of opioids in Thailand.Aims:To provide an up-to-date overview of the role of multidisciplinary teams in the regulation of opioids in Thai government hospitals.Settings and Design:A questionnaire survey study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…A cross-sectional study in China, found that 62.8% of clinicians had concerns about regulatory investigation for prescribing opioids. 30…”
Section: Legal Regulatory and Socio-politicalmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional study in China, found that 62.8% of clinicians had concerns about regulatory investigation for prescribing opioids. 30…”
Section: Legal Regulatory and Socio-politicalmentioning
confidence: 99%
“…In China, 16.5% of clinicians reported patient inability to pay for analgesics as a barrier. 30 A review of the affordability of opioids found a negative correlation between a days’ wages and the country income category: the lower the income, the more working days required to pay for the treatment. 22 Patients paid the full cost of all medications in Bangladesh, Cambodia, Indonesia, Laos, Nepal and the Philippines.…”
Section: Opioid Accessibilitymentioning
confidence: 99%
“…32 To improve accessibility and quality of palliative care service for tertiary care hospitals in Thailand, all health care staff in all inpatient care services should be prepared to perform timely specialist palliative consultations. 1 Thongkhamcharoen et al 33 surveyed the regulation of opioids in Thai government hospitals and found that physicians are the gatekeepers for patient access to opioids. Specialist palliative care teams should thus coordinate with primary physicians to achieve the best quality of care for both palliative care patients and their families.…”
Section: Discussionmentioning
confidence: 99%
“…Two areas deserve particular attention, access to pain control and availability of specialised trained staff. While a lack of both health care personnel fully trained in palliative care and specialist palliative care services has been reported in Thailand[ 119 ] with difficulties in opioid access[ 120 ], Japan has been successful in increasing full-time palliative care physicians and nurses and the median number of annual referrals[ 121 ]. Although late referral to palliative care services has been described as one problem in Korea[ 122 ], long-term cancer survivors can benefit from the Health Partner Program to become health coaches[ 123 ].…”
Section: Palliative Carementioning
confidence: 99%